PENGARUH PEMBERIAN PUPUK ORGANIK KOTORAN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L) - I Made Suryana; I Gusti Ayu Diah Yuniti; Listihani; Ramdhoani; Oktavianus Bulu Daka (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
The title of this research is “the effect of organic cow dung fertilizer on the growth and yield of shallot (Allium ascanolicum L). The purpose of this study was to determine the effect of the use of organic cow dung fertilizer and the best dose in the use of organic cow dung fertilizer on onion planting media. This research was conducted in Kesiman Village, East Denpasar District, Denpasar City. This research was conducted over a period of three months, starting from January 22 to March 25, 2021. To test the effect of giving organic cow dung fertilizer using the Randomized Block Design (RAK) method with six treatments, namely treatment (P0) = without giving organic manure fertilizer cattle, (P1) = 5 tons/ha organic cow dung, (P2) = 10 tons/ha organic cow dung, (P3) = 15 tons/ha organic cow dung, (P4) = 20 tons/ha fertilizer organic cow dung, (P5) = 25 tons/ha organic cow dung. Each treatment was repeated four times so that the total number of treatments became 24. The results of statistical analysis showed that the application of organic cow dung fertilizer on shallot plants had a significant effect on all parameters observed, except for the parameters of plant height and leaf fresh weight. The results showed that the application of organic cow manure 20 tons/ha (P4) was able to give the best results on the fresh weight of tubers, namely 66.68 g. And the oven-dry weight of tubers was 39.37 g.